Nature Guiding - Vinal, William Gould (Cornell University Press, 2019)
Nature Guiding is the science of inculcating nature enthusiasm, nature principles, and nature facts into the spirit of individuals. "Doing" nature-study means observing, wondering, and solving problems. It could include collecting, building, measuring, painting, planning, writing, touching, experimenting or any of a wide range of other activities. Most importantly, it allows children to be "original investigators."This book is intended as a resource for teachers and students engaged in nature study at summer camps and in schools. William Gould Vinal believed that the teacher of nature study should be "in sympathy with the simple life and the country way," that the nature study should emphasize observation of the interactions of plants and animals in their environment, and not be reduced to matters of taxonomy and anatomy. In Nature Guiding, he offers advice to camp counselors and school teachers on incorporating nature study into everyday activities, as well as suggestions for parents and others about using visits to state and national parks to teach nature lore.